An open access database for Himalayan environmental management - Sarkar, Sahotra (Himalayan Journal of Sciences, 2008)
Environmental management in the Himalayas requires creation of a database with collaborative public sharing of data Himalayan Journal of Sciences Vol.4(6) 2007 p.7-8